1979
DOI: 10.1111/j.1467-8489.1979.tb00234.x
|View full text |Cite
|
Sign up to set email alerts
|

The Short‐term Effect of Domestic Oil Price Increases on the Australian Economy With Special Reference to the Agricultural Sector

Abstract: The rise in the domestic price of oil products implied by the new import parity pricing policy for domestic crude oil is likely to pose some problems for macroeconomic management. In this paper an attempt has been made to quantify the short‐run adjustment problems involved, using the ORANI 78 model of the Australian economy. Results are presented for a range of variables of interest, including macroeconomic variables, industrial and workforce composition and farm incomes. With fixed real wages, farm incomes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…CGE models are widely employed in addressing the food before fuel issues, although with different modeling strategies and focuses (Elobeid and Tokgoz, 2007;Ignaciuk and Dellink, 2006;Arndt et al 2008;Rosegrant el al., 2008;Tyner and Taheripour, 2008;Yang et al, 2008;Saunders et al, 2009;Gohin and Chantret, 2010;Mcphail and Babcock, 2008;Vincent et al, 1979;Hanson et al, 1993;Saunders et al, 2009). Their advantage is a historical data set containing prices and quantities is not required.…”
Section: Computable General Equilibrium Models (Cge)mentioning
confidence: 99%
See 3 more Smart Citations
“…CGE models are widely employed in addressing the food before fuel issues, although with different modeling strategies and focuses (Elobeid and Tokgoz, 2007;Ignaciuk and Dellink, 2006;Arndt et al 2008;Rosegrant el al., 2008;Tyner and Taheripour, 2008;Yang et al, 2008;Saunders et al, 2009;Gohin and Chantret, 2010;Mcphail and Babcock, 2008;Vincent et al, 1979;Hanson et al, 1993;Saunders et al, 2009). Their advantage is a historical data set containing prices and quantities is not required.…”
Section: Computable General Equilibrium Models (Cge)mentioning
confidence: 99%
“…This ability of agriculture to supply growing demand is supported by Licker et al, 2010 who indicate approximately 50% more corn, 40% more rice, 20% more soybeans, and 60% more wheat could be produced if the top 95% of the crops' harvested areas met their current climatic potential. In 1979, Vincent et al, (1979) indicated the days of cheap corn are not over. Prices may be more stable as corn production expands to meet ethanol requirements and second generation ethanol, increased buffer stocks, and new technologies emerge (Vincent et al, 1979).…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…In this formulation, a scalar index defines the generalised capacity to produce and this then serves to locate the multi-product transformation schedule. This two-level specification was empirically estimated using data from the Bureau's grazing industry surveys (Vincent et al 1979).…”
Section: Modelling Macroeconomic Systemsmentioning
confidence: 99%